Validation of a Photographic Vitreous Haze Grading Technique for Clinical Trials in Uveitis - Madow, Brian (Am J Ophthalmol, 2011)
PURPOSE: To validate a photographic vitreous haze grading technique using a 9-step logarithmic scale in patients enrolled in a randomized, controlled clinical trial in uveitis. DESIGN: Retrospective study of clinical trials methodology. METHODS: SETTING: University-based department of ophthalmology. STUDY POPULATION: Baseline fundus photographs of patients with intermediate uveitis, posterior uveitis, or panuveitis enrolled in the Multicenter Uveitis Steroid Treatment (MUST) trial. OBSERVATIONAL PROCEDURE: Grading of vitreous haze using a previously described photographic scale. Regrading of a subset of photographs to assess intraobserver agreement. MAIN OUTCOME MEASURES: Interobserver and intraobserver intraclass correlation for photographic haze grading, and correlation between photographic and clinical vitreous haze scores, assessment of the clinical findings that significantly affect the photographic haze score. RESULTS: Vitreous haze was graded in 271 eyes (142 patients) by 3 postgraduate ophthalmologists. The interobserver and intraobserver intraclass correlations were excellent, with correlation coefficients between 0.84 and 0.93. There was moderately strong correlation between the photographic and clinical vitreous haze scores (r = 0.51; P < .001), with significant differences among the mean and median photographic haze scores for the 3 lowest clinical grades of haze, 0, 1+, and 2+. Other parameters that correlated with photographic vitreous haze score included visual acuity of 20/50 or worse (P = .003), degrees of posterior synechiae (P < .001), lens abnormality (P = .023) or posterior capsule obscuration (P = .001), and amount of anterior vitreous cell (P = .002). CONCLUSIONS: Photographic grading of vitreous haze with a 9-step logarithmic scale is a highly reproducible methodology that may be adaptable to use in future clinical trials.